2018
DOI: 10.1002/cam4.1300
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism underlying the negative effect of prostate volume on the outcome of extensive transperineal ultrasound‐guided template prostate biopsy

Abstract: Previous studies have indicated a possible relationship between increased prostate volume (PV) and decreased biopsy yield, although the mechanism involved is unclear. We evaluated 1650 patients who underwent template biopsy. The distribution of 993 cancer lesions in 302 prostatectomy specimens was compared with the biopsy data to determine whether each lesion was detected. A receiver operating characteristic (ROC) model was used to determine the diagnostic accuracy of prostate‐specific antigen (PSA) and relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, this study is the first report about the predictive role of the lymphocyte‐to‐monocyte ratio in men with larger prostate volumes. This finding of the present study may be clinically meaningful, given the prostate volume may have a negative impact on the detection of prostate cancer despite the existing controversy about its role 26,27 . In this respect, considering the lymphocyte‐to‐monocyte ratio together with well‐known risk factors of clinically significant prostate cancers such as PSA before prostatic biopsies may help reduce the number of unnecessary biopsies in men with larger prostate volumes in real clinical practice.…”
Section: Discussionmentioning
confidence: 61%
“…To the best of our knowledge, this study is the first report about the predictive role of the lymphocyte‐to‐monocyte ratio in men with larger prostate volumes. This finding of the present study may be clinically meaningful, given the prostate volume may have a negative impact on the detection of prostate cancer despite the existing controversy about its role 26,27 . In this respect, considering the lymphocyte‐to‐monocyte ratio together with well‐known risk factors of clinically significant prostate cancers such as PSA before prostatic biopsies may help reduce the number of unnecessary biopsies in men with larger prostate volumes in real clinical practice.…”
Section: Discussionmentioning
confidence: 61%
“…Demura et al, was found that increase in prostate volume (PV) is associated with a decrease in size and detectability of cancer lesions resulting in a decrease in biopsy yield. 20 In this study, PV in the PCa detected group was found less than the benign group.…”
Section: Discussionmentioning
confidence: 45%
“…In a study on the reduction of biopsy yield by Demura et al were found that PV is associated with a decrease in size and detectability of cancer lesions resulting in a decrease in biopsy yield. 8 For this reason, different PSA forms are utilized for biopsy prediction. In this sense, fPSA cannot be used because of close relationship with prostate volume.…”
Section: Resultsmentioning
confidence: 99%